Resenha do livro “Emoções & educação: reflexões sobre a obra de Augustín Escolano Benito” - Dewes, Elisângela Cândido da Silva (Revista Linhas, 2023)
The text deals with a review of the book Emoções & Educação - The historical construction of emotional education, translated into Portuguese by Heloísa Helena Pimenta Rocha and Andréa Bezerra Cordeiro, is a publication by Editora Mercado de Letras from the year 2021, about the original work Emociones Y Educación – La Construcción Histórica de La Educación Emocional, from 2018, by professor and researcher Augustín Escolano Benito, full professor at the Universidad de Valladolid and founder and director of the Centro Internacional de la Cultura Escolar (CEINCE), based in Berlanga de Duero - Spain. Work dedicated to thinking and analyzing the spaces, times, objects and rituals that make up a given school culture and that are permeated with emotions and feelings, presenting a new study perspective for researchers in the History of Education.